Cisplatin or LA-12 enhance killing effects of TRAIL in prostate cancer cells through Bid-dependent stimulation of mitochondrial apoptotic pathway but not caspase-10 - Vondálová Blanářová, Olga; Šafaříková, Barbora; Herůdková, Jarmila; Krkoška, Martin; Tománková, Silvie; Kahounová, Zuzana; Anděra, Ladislav; Bouchal, Jan; Kharaishvili, Gvantsa; Král, Milan; Sova, Petr; Kozubík, Alois; et al. (PloS one, 2017)
Searching for new strategies for effective elimination of human prostate cancer cells, we investigated the cooperative cytotoxic action of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and two platinum-based complexes, cisplatin or LA-12, and related molecular mechanisms. We demonstrated a notable ability of cisplatin or LA-12 to enhance the sensitivity of several human prostate cancer cell lines to TRAIL-induced cell death via an engagement of mitochondrial apoptotic pathway. This was accompanied by augmented Bid cleavage, Bak activation, loss of mitochondrial membrane potential, activation of caspase-8, -10, -9, and -3, and XIAP cleavage. RNAi-mediated silencing of Bid or Bak in Bax-deficient DU 145 cells suppressed the drug combination-induced cytotoxicity, further underscoring the involvement of mitochondrial signaling. The caspase-10 was dispensable for enhancement of cisplatin/LA-12 and TRAIL combination-induced cell death and stimulation of Bid cleavage. Importantly, we newly demonstrated LA-12-mediated enhancement of TRAIL-induced cell death in cancer cells derived from human patient prostate tumor specimens. Our results provide convincing evidence that employing TRAIL combined with cisplatin/LA-12 could contribute to more effective killing of prostate cancer cells compared to the individual action of the drugs, and offer new mechanistic insights into their cooperative anticancer action.
Keywords: Amantadine; Caspase 10; apoptóza; amantadin; cisplatina; BH3 Interacting Domain Death Agonist Protein; kaspasa 10; Mitochondria; Cisplatin; Apoptosis; lidé; nádory prostaty; protein TRAIL; Prostatic Neoplasms; organoplatinové sloučeniny; mitochondrie; Male; Organoplatinum Compounds; protein Bid; mužské pohlaví; TNF-Related Apoptosis-Inducing Ligand; Humans